2016
DOI: 10.1111/vru.12468
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Appearance of Presumed Noncardiogenic Pulmonary Edema and Correlation With the Underlying Cause in Dogs and Cats

Abstract: Noncardiogenic pulmonary edema is an important cause of respiratory disease in dogs and cats but few reports describe its radiographic appearance. The purpose of this retrospective case series study was to describe radiographic findings in a large cohort of dogs and cats with presumed noncardiogenic pulmonary edema and to test associations among radiographic findings versus cause of edema. Medical records were retrieved for dogs and cats with presumed noncardiogenic edema based on history, radiographic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…In dorsal recumbency, the caudal lung lobes seem to be more affected 26. A recent case series focused on the radiographic appearance of non‐cardiogenic pulmonary oedema suggested that a dorsal distribution of the lung lesions seemed to be more often observed in NPPO than in other causes of non‐cardiogenic pulmonary oedema, although, the authors could not give an explanation to this finding 5…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In dorsal recumbency, the caudal lung lobes seem to be more affected 26. A recent case series focused on the radiographic appearance of non‐cardiogenic pulmonary oedema suggested that a dorsal distribution of the lung lesions seemed to be more often observed in NPPO than in other causes of non‐cardiogenic pulmonary oedema, although, the authors could not give an explanation to this finding 5…”
Section: Discussionmentioning
confidence: 94%
“…Postobstructive pulmonary oedema type 1 is also known as negative pressure pulmonary oedema (NPPO) and has been highlighted as a potential complication in the postanaesthetic period in people and horses 3 4. Multiple causes have been attributed to the development of NPPO: brachycephalic obstructive airway syndrome (BOAS), strangulation, choking, near drowning, airway collapse, laryngeal mass, laryngeal paralysis, endotracheal tube (ETT) obstruction, laryngospasm and partial occlusion of the upper airway tract with a foreign body or other mass 2 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracic radiographic evaluation was based on previously described methods . When radiographs from multiple time points were available for a patient, the last set of radiographs were used for scoring evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Cranial lung lobe pulmonary vessels were considered normal if diameters were less than the width of the proximal one‐third of the 4th rib . Caudal pulmonary vessels were normal if diameters were less than the width of the 9th rib where they crossed . Blood vessels were considered tortuous if any deviation from their expected course was identified.…”
Section: Methodsmentioning
confidence: 99%